Functional MRI-based study of emotional experience in patients with psychogenic non-epileptic seizures: Protocol for an observational case-control study-EMOCRISES study. - Pierre Fauvé; Louise Tyvaert; Cyril Husson; Emmanuelle Hologne; Xiaoqing Gao; Louis Maillard; Raymund Schwan; Claire Banasiak; Wissam El-Hage; Gabriela Hossu; Coraline Hingray (PLoS ONE, 2022)
Background Psychogenic non epileptic seizures (PNES) are a frequent, disabling and costly disorder for which there is no consensual caring. They are considered as a dissociative disorder and they share many common characteristics with post-traumatic stress disorder (PTSD). Nevertheless, their pathophysiology is still unclear. In this study, we plan to obtain new data comparing functional brain activity of participants suffering from PNES, from PTSD and healthy controls via functional brain MRI during resting state and under emotional visual stimulation. The protocol presented hereunder describes an observational study with no direct treatment implication. Nevertheless, it could lead to a better understanding of PNES and to identifying targets for specialised cares of post-traumatic or dissociative disorders, like repetitive transcranial magnetic stimulation. Methods & analysis This is a prospective, single-centre, interventional, non-randomized, open, controlled and exploratory clinical study. It will involve 75 adult French, right-handed women in 3 groups, either suffering from PNES or PTSD, or healthy controls. An informed consent will be signed by each participant. All of them will be given psychiatric tests to assess dissociation and alexithymia, psychopathological profile and history, and emotional recognition. Each participant will undergo a functional brain MRI. We will record anatomical images and five functional imaging sequences including emotional periodic oscillatory stimulation, standard emotional stimulation, Go / No Go task under emotional stimulation, and resting state. Analysis will include a descriptive analysis of all participants and the treatment for functional magnetic resonance imaging images of each sequence. Registration, ethics & dissemination This study was approved the regional Protection of Persons Committee under the reference 16.10.01 and by the French National Medical Security Agency under the reference 2016-A01295-46. The protocol and results will be published in peer-reviewed academic medical journals and disseminated to research teams, databases, specialised media and concerned patients' organisations.